Effect of Nutrient Management and Weeds on Incidence of Fungal Diseases in Rice - Priyadarshani, T.D.C.; Wickramasinghe, W.M.D.M.; Egodawatta, W.C.P.; Tharsini, P.; Beneragama, D.I.D.S.; Devasinghe, D.A.U.D. (Department of Agronomy and Horticulture, IPB University, 2023)
High-input, modern agriculture uses large amounts of energy, water, fertilizers, and pesticides to produce high crop yields. One of the major bottlenecks of the modern agriculture in the tropics is substantial yield losses due to fungal diseases including rice blast, leaf spots and leaf scald. The aim of this study was to compare the incidence of fungal diseases in judicious nutrient management systems, including organic, integrated, and conventional, under different weed categories during dry season (May to September 2020) and wet season (November 2020 to March 2021). Rice disease incidence were collected for both seasons from 48-84 days after sowing. Additionally, disease incidences on grasses and sedges weeds were also calculated. Brown spot, narrow brown leaf spot, leaf scald, and rice blast incidences were substantial in wet season, while the disease incidences during dry season in 2020 were negligible. The disease incidences were significantly higher (P<0.05) in organic and conventional input systems compared to the integrated input system. Disease incidences of brown spot and leaf scald were found in the dry season. Higher disease incidences were recorded in the wet season than in the dry season. The incidences of the brown spot were higher on sedges than in grasses and vice versa were observed for narrow brown leaf spot disease. Leaf scald incidences were positively correlated with the significant nitrogen status of the rice crop. Disease incidence was low in integrated input system compared to conventional and organic input systems, while weeds were reported as alternative hosts. It can be concluded that the integrated nutrient management with recommended dosage of nitrogen application with proper weed management can lead to low disease incidents, hence is ecologically more sustainable.